Fillers (IntechOpen, 2023)
Fillers - Synthesis, Characterization and Industrial Application comprises a set of chapters that brings an interdisciplinary perspective to accomplish a more detailed understanding of filler materials for the synthesis and characterization of different industrial applications. This book embraces all the chapters that are concerned with the effect of incorporating different fillers or particulates in fabricated composites. Significant research efforts all around the world are continuing to explore the properties of composite materials. Researchers are collectively focusing their efforts on the use of particulate fillers in composites for miscellaneous applications. This book delivers a comprehensive study associated with the sections of material science, polymer technology, anisotropic elasticity phenomena, fracture mechanics, applied mechanics, material synthesis, mechanical and thermo-mechanical characteristics, tribological behavior, etc.